2APL: a practical agent programming language - Dastani, Mehdi (Autonomous agents and multi-agent systems, 2008)
This article presents a BDI-based agent-oriented programming language, called 2APL (A Practical Agent Programming Language). This programming language facilitates the implementation of multi-agent systems consisting of individual agents that may share and access external environments. It realizes an effective integration of declarative and imperative style programming by introducing and integrating declarative beliefs and goals with events and plans. It also provides practical programming constructs to allow the generation, repair, and (different modes of) execution of plans based on beliefs, goals, and events. The formal syntax and semantics of the programming language are given and its relation with existing BDI-based agent-oriented programming languages is discussed.